Opposing book bans: a resilient and subversive information practice - Shannon M. Oltmann; Fatima Espinoza Vasquez (Information Research: An International Electronic Journal)
Introduction. In this paper, we discuss the concepts of censorship, resilience and information precarity. We explain the framework of information precarity and emphasise the agentic responses of marginalised communities, then show that book bans restrict vital access to valuable information. Yet marginalised communities respond through resilience and subversive practices to oppose book bans.